The Politics of Criminal Law in Self-Defense in Indonesia: Regulatory And Enforcement Discourses - Ahmadi, Cecep Ibnu; Ismail, Dian Ekawaty; Machmud, Andika W. (Universitas Negeri Gorontalo, 2023)
This article is a study of the legal politics of regulating self-defense actions in Indonesia as well as describing the practice of law enforcement against acts of self-defense. This article will be analyzed normatively using a statutory approach and case approach. The results of the analysis show that tha act of self-defense regulated in the Criminal Code as the basis of criminal law in Indonesia shows the principles of the rule of law, as well as being a form of protection for citizens in defending their lives, especially in situations of threats and crimes.Factually, there are actions from law enforcement not continuing the law enforcement process of self-defense actions as felt by Irfan and Rofiqi in Tangerang and by Amaq Shinta in lombok. However, there are still differences in the settlement and handling of cases rleated to acts of self-defense as experienced by ZL in Malang. This Actually shows that there is injustice because there is process that influences criminal policy so that it has an impact on not fulfilling a sense of justice for every citizen as one of the guarantees in a legal state like Indonesia.